Optimalisasi Akuntanbilitas Masjid At-Thaibah Melalui Laporan Keuangan dengan Ms. Excel Berdasarkan ISAK 335 - Anggi Novia Fitriani; Ayatulloh Michael Musyaffi; Eka Septariana Puspa (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to optimize the accountability of At-Thaibah Mosque by developing financial statements using Microsoft Excel based on ISAK 335. The problem identified was that the mosque’s financial recording was still limited to simple cash inflow and outflow records, so it had not presented comprehensive financial information. This study used the Research and Development (R&D) method with the Waterfall model, consisting of analysis, design, implementation, verification, and maintenance stages. Data were collected through observation, interviews, and documentation. The result is an integrated Microsoft Excel-based financial reporting template that produces five financial statements according to ISAK 335. The template improves recording order, reporting efficiency, transparency, and financial accountability at At-Thaibah Mosque.